"O que ocultam as cabaças?" [recurso eletrônico] : uma aproximação arqueosemiótica materialista aos usos, funcionalidades e representações das cabaças durante o período intermédio tardio no Deserto do Atacama, Chile - Acuña, Cristián Olivares (2018)
The present work analyses the decorated gourds of the Atacama Desert (Chile), attributed to the Late Intermediate Period (A.D. 1000 - 1430), from a materialistic and archeosemiotic approach linked to visual materialilty and altered states of consciousness (ASC). These supports not only have a long historical trajectory in the Andean cultures (archaeological evidence streach back 15 thousand years), as they have also been important in the cultural transmission of habits, identities, imaginaries and ideologies, through their forms, uses and pyrographic design. The emphasis of this research with this type of support is based on its wide presence in the archaeological records of the zone and the omission or deliberate exclusion in the archaeological investigations, mainly due to the bias in studies on ceramics, textiles and rock art. Furthermore, interpretation towards the utilitarian and/or ritual functionality of the gourds is provided, as well as the similarities and iconographic differences between the desert areas.